A Review on Modification of Zeolite for Photocatalytic Applications - Dzinun, Hazlini; Othman, Mohd Hafiz Dzarfan (Multidisciplinary Applied Research and Innovation, 2020)
Zeolite are microporous crystalline alumina-silicate materials, widely used as catalysts, ion exchangers and adsorbents due to their chemical structure and surface properties. The unique properties of zeolite such as high adsorption capacity and cation exchange make it used as a support material. This review article presents the details of various researches of zeolite used as photocatalyst in photocatalytic application. The modifications of zeolite using several methods are described in details for photocatalytic enhancement. The effect of zeolite nanoparticles in membrane fabrication also provided in this article. Furthermore, the efficiency of zeolite used as adsorbents and photocatalyst in the photocatalytic application also presented.